Separação de misturas no ensino fundamental: mapas conceituais e resolução de problemas - Costa, Luís Felipe Souza Paulino da (2019)
This professional master's work is focused on the following research question: "How and to what extent does the effect of concept maps on the solving of experimental problems related the separation of mixtures in junior high school?". Its objectives are: to qualitatively and quantitatively analyze concept maps developed by the students; to qualitatively and quantitatively analyze the solutions developed by the students for the experimental problems; to determine whether there are correlations between the concept maps and the solutions for the experimental problems developed by the students. All the work development, carried out with students from two private junior high schools, is based on the theory of meaningful learning, with emphasis on concept maps. An advance organizer was used, demonstrative classes were taught (using an instructional text), and a familiarization of the students with concept maps was done. Afterwards, the students developed concept maps related to the concepts involved in the resolution of six experimental problems, which were later solved by the students. The concept maps and problem solutions were qualitatively and quantitatively analyzed, aiming to determine whether there were correlations between them. The analysis of the concept maps was done comparatively to reference concept maps, organized according to the principles of the theory of meaningful learning (progressive differentiation and integrative reconciliation). A good correlation was found only between the results obtained in the concept maps and the solutions of the problems when the maps were linear. For the branched concept maps, the students had difficulty in the hierarchization of concepts, from more general concepts to less-specific ones, as well as in the integrative reconciliation; nevertheless, they presented an increasing performance along the resolution of the problems. Finally, the students (~50%) expressed themselves on the use of concept maps. According to the majority opinion, they are a facilitative tool for learning and for the organization of what is being learned, also being useful for other subjects.